Rewinding and unwinding: art and justice in times of political transition - Garnsey, Eliza (International journal of transitional justice, 2016)
The purpose of this article is to theorize the relationship between art and justice in times of transition so that a broader spectrum of political possibilities and their implications can be imagined. The aim is to offer a way to think about, and to render visible, the web of relationships that constitute this bond. By undertaking a close analysis and narrative investigation of the art installation REwind: A Cantata for Voice, Tape and Testimony , I use the artwork to elucidate four key ideas relating to paradigms, agency, encounters and space which make art relevant and meaningful to transitional justice. These four ideas frame two central arguments. First, I argue that an account of transitional justice without aesthetic dimensions is insufficient, precisely because transitional justice ‘acknowledges itself as a process inseparable from feelings of justice.’ Artworks can fill out affective topologies in ways that facilitate or stimulate recognition and a ‘feeling of being there.’ Secondly, I contend that art plays an important role in animating and activating individual narratives so that they take on collective importance. In doing so, the past can be shared so that a new political future can be imagined.